1998
DOI: 10.1176/jnp.10.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Apathy, Depression, and Cognitive Performance in HIV-1 Infection

Abstract: The authors examined the relationship between apathy, depression, and cognitive performance in 48 HIV-1-seropositive and 21 seronegative (control) subjects, using reaction time (RT) and working memory tasks. Apathy, but not depression, was associated with working memory deficits among HIV-seropositive subjects. The cognitive-affective component of the Beck Depression Inventory (BDI), but not apathy, was associated with slowing and decreased accuracy on a choice RT task. The BDI cognitive-affective component wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
93
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 53 publications
15
93
1
4
Order By: Relevance
“…However, these findings are consistent with other studies that used frontal-subcortical systems-dependent tests investigating cognitive flexibility, Stroop interference, working memory, and a different form of dual-task performance, each finding a similar relationship between performance on these tasks and the presence of apathy and/or irritability symptomatology (Castellon et al, 1998Paul et al, 2005a). The current study furthered this work by providing a direct comparison of apathy and irritability with anxiety and depression and by quantifying the extent to which apathy and irritability share predictive variance with dual-task performance.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, these findings are consistent with other studies that used frontal-subcortical systems-dependent tests investigating cognitive flexibility, Stroop interference, working memory, and a different form of dual-task performance, each finding a similar relationship between performance on these tasks and the presence of apathy and/or irritability symptomatology (Castellon et al, 1998Paul et al, 2005a). The current study furthered this work by providing a direct comparison of apathy and irritability with anxiety and depression and by quantifying the extent to which apathy and irritability share predictive variance with dual-task performance.…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that depression and anxiety symptomatology may relate to other neural systems affected by HIV that were not measured in the current study, although other work evaluating primary neuropsychological domains have thus far not found that to be the case (Castellon et al, 1998;Grant et al, 1993;Hinkin et al, 1992;Mapou et al, 1993;Perdices et al, 1992;Rabkin et al, 2000). Alternatively, these psychiatric features may be more related to psychological and psychosocial factors (Perdices et al, 1992).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations